Nuciferine relieves type 2 diabetes mellitus via enhancing GLUT4 expression and translocation - Tongxi Zhou; Guanjun Song; Di Tian; Qinghua Liu; Jinhua Shen; Xinzhou Yang; Ping Zhao (Food Science and Human Wellness)
Nuciferine contained in lotus leaves have been confirmed to have the effect of ameliorating hyperlipemia and hyperglycemia. A laser scanning confocal microscope was used to track the translocation of glucose transporter 4 (GLUT4) in L6 cells and the changes in intracellular Ca2+ levels in real time, and related protease inhibitors combined with western blotting were used to explore the mechanism of nuciferine. Meanwhile, KK-Ay mice, the spontaneous type 2 diabetic mice, were used to evaluate the in vivo activity of nuciferine. In this study, the in vitro studies indicated that nuciferine-induced GLUT4 translocation was regulated by G protein-PLC-PKC and AMPK pathways and nuciferine-enhanced intracellular Ca2+ was mediated by G protein-PLC-IP3-IP3R pathway, the increase in intracellular Ca2+ caused by nuciferine was not directly related to GLUT4 translocation, but both promote glucose uptake. The in vivo results suggested that nuciferine ameliorated weight gain induced by high-fat diet, abnormal lipid metabolism and the symptoms of insulin resistance in KK-Ay diabetic mice. Western blot results suggested that nuciferine increased AMPK and PKC phosphorylation levels in skeletal muscle and liver, and enhanced GLUT4 expression in skeletal muscle. Taken together, this research showed that nuciferine has the non-negligible potential in the treatment of type 2 diabetes mellitus.